Valery Bryusov’s Evaluations on Armenian Poetry a Century Later - JANPOLADYAN, MAGDA (Bulletin of Yerevan University H: Russian Philology, 2021)
The article is written on the occasion of 100th anniversary of the famous anthology called “Poetry of Armenia” (M., 1916). The author consideres the critical evaluations of V. Bryusov on the centuries-old Armenian poetry – general observations and characteristics, as well as views on different works of some poets. As well the author presents how Bryusovs evaluations were perceived by Armenian literary scholars. Many Bryusovs evaluations with their deep penetration to the world of Armenian poetry, their precision and brightness, have not lost, even today, a century later, the scientific and critical value and still remain relevant.
Keywords: Anthology, 100th anniversary, Bryusov, Armenian poetry, critical evaluations, opinions of Armenian literary scholars, relevance